Patient's Opinion on Nursing Care - Sharma, Bhaumika; Dhakal, S. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Care; Communication; Interpersonal; Nursing DOI: 10.3126/jnhrc.v6i1.2443 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 42-48